Computational models of cognitive processes : proceedings of the 13th neural computation and psychology workshop - Mayor, Julien; Gomez, Pablo (Pablo Alegria) (Progress in neural processing ;, 2014)
Computational Models of Cognitive Processes collects refereed versions of papers presented at the 13th Neural Computation and Psychology Workshop (NCPW13) that took place July 2012, in San Sebastian (Spain). This workshop series is a well-established and unique forum that brings together researchers from such diverse disciplines as artificial intelligence, cognitive science, computer science, neurobiology, philosophy and psychology to discuss their latest work on models of cognitive processes.